خطة مقترحة لإدارة الأنشطة الترويحية بالأندية الرياضية بمحافظة الإسكندرية - المعاملى، إيمان عبدالعزيز عبدالوهاب; القمحاوي، نوره فايز عبدالعاطي (جامعة الأسكندرية - كلية التربية الرياضية للبنات, 2021)
التخطيط لاستثمار قضاء وقت الفراغ من خلال ممارسة الأنشطة الترويحية جزء لا يتجزأ عن التخطيط القومي بغرض تحقيق الأهداف المرجوة من البرامج الترويحية، وتعتبر الخطة وثيقة مكتوبة تترجم ما تم التخطيط له ووضع تصور للمستقبل وأهداف محددة تسعي المنظمة لتحقيقها، ويهدف البحث إلى وضع خطة مقترحة لإدارة الأنشطة الترويحية بالأندية الرياضية بمحافظة الإسكندرية، وذلك على عينة عددها (133) من أعضاء مجلس الإدارة والمديرين التنفيذيين والإخصائيين الرياضيين ومسئولي النشاط بالأندية الرياضية بمحافظة الإسكندرية، واستخدمت الباحثتان في جمع البيانات استمارة الخطة المقترحة لإدارة الأنشطة الترويحية بالأندية الرياضية بمحافظة الإسكندرية، وبعد معالجة البيانات إحصائيا تم التوصل إلى نتائج موافقة عينة البحث على الخطة المقترحة لإدارة الأنشطة الترويحية بالأندية الرياضية بمحافظة الإسكندرية من خلال المحاور (أهداف إدارة الأنشطة الترويحية، السياسات والإجراءات المنظمة لإدارة الأنشطة الترويحية، الإمكانات لإدارة الأنشطة الترويحية، الهيكل التنظيمي لإدارة الأنشطة الترويحية، محتوى الأنشطة الترويحية، البرنامج الزمنى لتنفيذ خطة الأنشطة الترويحية، التقويم وقياس الأداء لإدارة الأنشطة الترويحية، مؤشرات نجاح إدارة الأنشطة الترويحية) وتم التوصل إلى خطة لإدارة الأنشطة الترويحية بالأندية الرياضية بمحافظة الإسكندرية.
Planning to invest leisure time through the practice of recreational activities is an integral part of national planning for the purpose of achieving the desired goals of recreational programs, The plan is a written document that translates what has been planned and puts a vision for the future and specific goals that the organization seeks to achieve, The research aims to develop a proposed plan for managing recreational activities in sports clubs in Alexandria Governorate, This is based on a sample of (133) members of the board of directors, executives, sports specialists and activity officials in sports clubs in Alexandria Governorate, In collecting data, the two researchers used the proposed plan form for managing recreational activities for sports clubs in Alexandria Governorate, After processing the data statistically, the results of the research sample's approval of the proposed plan for managing recreational activities for sports clubs in Alexandria Governorate were reached through the axes (objectives of the management of recreational activities, policies and procedures governing the management of recreational activities, The capabilities for managing recreational activities, the content of recreational activities, the timetable for implementing the plan of recreational activities, the evaluation and measurement of performance for the management of recreational activities, the indicators of success of the management of recreational activities, the organizational structure of the management of recreational activities), A plan was reached to manage the recreational activities of the sports clubs in Alexandria Governorate.
Keywords: المنشآت الرياضية -- القادة الإداريون -- التنشئة الاجتماعية -- الأنشطة الترويحية -- الترويج الإلكتروني